2000
DOI: 10.1128/mcb.20.13.4626-4634.2000
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Opposes the Apoptotic Effects of Bone Morphogenetic Protein 7 on Tissue Remodeling

Abstract: Interactions between estrogen and growth factor signaling pathways at the level of gene expression play important roles in the function of reproductive tissues. For example, estrogen regulates transforming growth factor beta (TGF␤) in the uterus during the proliferative phase of the mammalian reproductive cycle. Bone morphogenetic protein 7 (BMP-7), a member of the TGF␤ superfamily, is also involved in the development and function of reproductive tissues. However, relatively few studies have addressed the expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 75 publications
4
44
0
Order By: Relevance
“…In a previous paper, Ozkaynak et al (1997) reported that administration of exogenous estradiol markedly inhibits uterine BMP-7 transcripts in vivo. Similarly, studies on the chick oviduct have demonstrated an inhibitory effect of estrogen on BMP-7 gene expression (Monroe et al 2000). Therefore, our finding that BMP-7 expression was not suppressed by increases in circulating estradiol levels during the estrous cycle was unexpected.…”
Section: Discussionsupporting
confidence: 61%
“…In a previous paper, Ozkaynak et al (1997) reported that administration of exogenous estradiol markedly inhibits uterine BMP-7 transcripts in vivo. Similarly, studies on the chick oviduct have demonstrated an inhibitory effect of estrogen on BMP-7 gene expression (Monroe et al 2000). Therefore, our finding that BMP-7 expression was not suppressed by increases in circulating estradiol levels during the estrous cycle was unexpected.…”
Section: Discussionsupporting
confidence: 61%
“…All primary microarray data are accessible at www.ncbi.nlm.nih.gov/geo (GSE7382). We selected BMP7 for further study because BMP7 mediates epithelial-mesenchymal signaling (Dean et al, 2004), and epithelial cell apoptosis and proliferation in several different organ systems (Luo et al, 1995;Monroe et al, 2000). Consistent with these observations, we found that BMP7 can decrease proliferation and increase apoptosis of normal and cancerous mammary epithelial cells (Supplementary Figure S8).…”
Section: Identification Of Lmo4-responsive Genessupporting
confidence: 68%
“…Estradiol has been shown to downregulate both BMP7 and its receptor ActRIIB in a variety of hormone-responsive epithelial cells (Kusumegi et al, 2004). In fact, estradiol inhibits apoptosis in epithelial cells of reproductive epithelia by suppressing BMP7 signaling (Monroe et al, 2000). Interestingly, estradiol completely inhibited LMO4-mediated apoptosis in MCF7 cells (Figure 3c).…”
Section: Identification Of Lmo4-responsive Genesmentioning
confidence: 95%
“…Exogenous treatment with estradiol has been shown to decrease expression of uterine Bmp7 mRNA in vivo (Ozkaynak et al 1997). Similarly, estradiol treatment has been shown to repress BMP7 mRNA levels in chicken oviduct (Monroe et al 2000). In addition, BMP7 is shown to regulate apoptosis in primary oviductal cells (Monroe et al 2000).…”
Section: Bmp4 and Female Reproductive Systemmentioning
confidence: 98%